2022
DOI: 10.2105/ajph.2021.306563
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing COVID-19 Contact Tracing During a Surge Using Chatbot Technology

Abstract: When COVID-19 cases surge, identifying ways to improve the efficiency of contact tracing and prioritize vulnerable communities for isolation and quarantine support services is critical. During a fall 2020 COVID-19 resurgence in San Francisco, California, prioritization of telephone-based case investigation by zip code and using a chatbot to screen for case participants who needed isolation support reduced the number of case participants who would have been assigned for a telephone interview by 31.5% and likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…22 To prevent delayed outreach during surges, a new chatbot technology developed by CDPH was implemented to immediately reach out to people newly diagnosed with COVID-19 by text message. 23 Despite the operational challenges of contact tracing, reported data informed the local understanding of transmission networks and guided policies for schools and face masks for people who were fully vaccinated. 24 Vaccine rollout.…”
Section: Strategy 2: Prioritizing Resources In Neighborhoods Highly A...mentioning
confidence: 99%
“…22 To prevent delayed outreach during surges, a new chatbot technology developed by CDPH was implemented to immediately reach out to people newly diagnosed with COVID-19 by text message. 23 Despite the operational challenges of contact tracing, reported data informed the local understanding of transmission networks and guided policies for schools and face masks for people who were fully vaccinated. 24 Vaccine rollout.…”
Section: Strategy 2: Prioritizing Resources In Neighborhoods Highly A...mentioning
confidence: 99%
“…Finally, there are the chatbot types that contain only 1 article (AI Assistants), (Virtual Assistant), (Health Assistant) (Chatbot that manages information), and (Chatbot with AI, NLP, and NLC)". [25], [27], [29], [40], [46], [47], [55], [ [23], [30], [31], [33], [35], [41], [42], [44], [45], [49], [56]- [58], [ 4.5. Recent work on the processes that optimize a conversational chatbot RQ3.…”
Section: Recent Work On the Types Of Conversational Chatbots That Existmentioning
confidence: 99%
“…: Table 9 shows the processes that the chatbots optimize: according to [24], [27], [42] bots are employed in bot training processes to feed its knowledge base; on the other hand, in [23], [43]- [45], [50], [51], [56], [62], [66]. The use of conversational bots was found to be part of the teaching process [21], [22], [25], [26], [29]- [31], [40], [41], [53], [64], it was realized that healthcare processes have been altered and have incorporated the use of chatbot technology with patients and professionals. Similarly, according to, [39], [46], [61] there is a segment of users who use these bots in Processes for personal assistance for various reasons.…”
Section: Recent Work On the Types Of Conversational Chatbots That Existmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study conducted in San Francisco (California, United States) during the COVID-19 pandemic evaluated the use of a chatbot to inform (relatively low-risk) cases about CT-guidelines and -measures, assess their ability to isolate, and elicit at-risk contacts. This study found that, with help from the chatbot, PHS were able to reduce the proportion of cases assigned to a telephone interview by 31.5%, allowing PHPs to direct more resources towards relatively vulnerable communities [ 7 ]. Another study conducted in the United States investigated the perspectives of individuals who recently tested for COVID-19 on using website services for (anonymous) contact notification.…”
Section: Introductionmentioning
confidence: 99%